ANALISIS PENGARUH VARIASI HOLDING TIME ANNEALING TERHADAP LAJU KOROSI TITANIUM PADA LARUTAN CAIRAN TUBUH SINTETIS - Rohmannudin, Tubagus Noor; Noerochim, Lukman; Sulistijono, Sulistijono; Luthfiansyah, Candra Rizki; Tanjung, Rifqi Aulia (Jurnal Rekayasa Mesin, 2023)
Biomaterials are crucial for bone implants due to their biocompatible and inert nature, ensuring no adverse effects within the human body. Titanium is renowned for its exceptional corrosion resistance. This research aims to analyze the impact of annealing holding time and pH of synthetic body fluid on the hardness and corrosion rate of titanium. The annealing process was performed at 700°C, with holding times of 30, 60, and 90 minutes. As an electrolyte medium, a Hanks' solution with pH variations of 4, 6, and 8 was used and maintained at 37°C. Potentiodynamic corrosion testing demonstrated the lowest corrosion rate in specimens treated with 30 minutes of annealing at pH 8, measuring 0.32 x 10-2 mmpy. The 30-minute annealing exhibited the lowest corrosion rate, which was confirmed by Electrochemical Impedance Spectroscopy (EIS) results showing a higher Rp value, indicating a lower corrosion rate. This is attributed to the presence of a passive Rutile TiO2 layer formed during the annealing process, as confirmed by X-ray Diffraction (XRD) analysis. Metallography observations indicated that the microstructure of untreated specimens consisted of α and β phases. Scanning Electron Microscopy (SEM) analysis of specimens annealed for 30 minutes revealed an oxide layer on the surface without any visible pores. However, an increase in annealing holding time led to the formation of pores, particularly noticeable after 90 minutes of annealing. The presence of pores in the oxide layer resulted in an increased corrosion rate with longer annealing holding times. Conversely, hardness testing demonstrated that longer annealing holding times resulted in higher hardness values.